Crops use inorganic and labile organic phosphorus from both high‐ and low‐availability layers in no‐till compost‐amended soils - Li, Xue; Hallama, Moritz; Romanyà, Joan (Soil use and management, 2024)
Organic fertilization in no‐till soils increases soil organic matter and nutrient pools primarily in surface soils. However, little is known about how microbial activity affects crop access to phosphorus (P) forms at the surface, where the organic fertilizer is applied, and the subsurface, the main rooting zone. We aimed to study the changes in organic and inorganic P (Po; Pi) forms and compounds in no‐till compost amended surface (0–5 cm) and subsurface (5–15 cm) soils growing a crop rotation for 2 years in pots. Crops were grown in pots with compost amended to the soil surface, while unamended and compost‐amended pots without crops were used as controls. We measured changes in microbial C (carbon), soluble C, total Po and Pi forms, the moderately accessible EDTA‐NaOH‐Pi (‐Po), and labile NaHCO3‐Pi (‐Po). P compounds in the EDTA‐NaOH extract were measured by 31P‐NMR. Compost addition increased the levels of total Pi and although it had no effect on total Po, increases of inositol, other phosphate monoesters and orthophosphate diesters could be observed. After the application of compost, the amount of total organic C, soluble carbon and all P forms increased in surface soil, while in the subsurface soil, there was a reduction in organic C and an increase in soluble C, total Pi, EDTA‐NaOH‐Pi and NaHCO3‐Pi and the EDTA‐NaOH‐Po and labile NaHCO3‐Po. Growing crops reduced all measured Pi forms and labile NaHCO3‐Po, increased EDTA‐NaOH‐Po in surface soils and had no observable impact on total Po in either organic C‐enriched surface or organic C‐reduced subsurface soils. Crops mostly used Pi from the low P availability C‐reduced subsurface layer, where NaHCO3‐Po pools also decreased. Large reductions in NaHCO3‐Po and increased levels of IHP and other‐monoesters in crop‐growing organic C‐enriched surface layers may suggest microbial formation of monoesters Po and crop use of labile Po pools. In summary, Po formation in C‐enriched surface layers and the mobilization of all Pi forms throughout the soil profile are particularly important findings for the understanding of P dynamics in compost‐amended no‐till systems.